(untitled) (Journal of Governance and Development (JGD), 2015)
Social entrepreneurship has grown into a global movement that is producing solutions to the world’s toughest problems and transforming the way we think about social change. However, despite the popularity of this approach particularly through its microfinance schemes, it is a field that remains under-theorized and less scrutinized. This paper, therefore, attempts to critically examine key cross-cutting issues to microfinance. In doing so, it will delve into actual economic and social impacts of microfinance in Asia and Europe, rather than providing a robust critique of its technical methodologies, a popular approach recommended by almost all microfinance institutions. Among critical issues that will be explored include challenges of social entrepreneurship especially as it relates to the global mission of Millennium Development Goals (MDG) to reduce long-term poverty. Finally, the paper offers policy recommendation that will strengthen the current practice of social entrepreneurship which includes setting up a revolving fund to finance emerging social entrepreneurs so as to complement the existing model of direct financing of MFI. It is hopeful that these recommendations will drive sustainable change of poverty reduction beyond the millennium.